1997
DOI: 10.1093/jat/21.3.197
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Metabolite of Nimesulide*†

Abstract: Nimesulide is a nonsteroidal anti-inflammatory drug recently detected in equine blood and urine samples taken at the race track. The detection of the drug in a blood sample led to the identification of an unknown thin-layer chromatographic (TLC) spot in track urine samples as a metabolite of nimesulide. Characterization of the unknown TLC spot and comparison with the synthesized compound shows that the unknown TLC spot is a previously unreported equine metabolite of nimesulide. The metabolite was identified as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In another study, Gandini et al (1991) observed that the hydroxy metabolite reached its highest plasma concentration (3Á03 mg mL À1 ) at 5Á33 h, with an apparent half-life of 4Á78 h, following oral administration of nimesulide (200 mg). Recently, Sarkar et al (1997) have reported the presence of an unknown compound known as``the purple spot'' in race-track urine samples. This compound was not positively iden-ti®ed until nimesulide was found in the blood samples and it was postulated to be a urinary metabolite of nimesulide formed by the reduction of the nitro group on nimesulide to an amino group (4-amino-2-phenoxy-methanesulphonanilide).…”
Section: Pharmacokinetics Of Nimesulidementioning
confidence: 99%
“…In another study, Gandini et al (1991) observed that the hydroxy metabolite reached its highest plasma concentration (3Á03 mg mL À1 ) at 5Á33 h, with an apparent half-life of 4Á78 h, following oral administration of nimesulide (200 mg). Recently, Sarkar et al (1997) have reported the presence of an unknown compound known as``the purple spot'' in race-track urine samples. This compound was not positively iden-ti®ed until nimesulide was found in the blood samples and it was postulated to be a urinary metabolite of nimesulide formed by the reduction of the nitro group on nimesulide to an amino group (4-amino-2-phenoxy-methanesulphonanilide).…”
Section: Pharmacokinetics Of Nimesulidementioning
confidence: 99%
“…Simultaneous LC estimation of NMD and hydroxy NMD in rat plasma, CSF and brain was carried out [126]. Specific HPLC methods for simultaneous determination of NMD and its hydroxy metabolite in human plasma in healthy volunteers were developed [127]. Sarkar et al have reported the detection of an unique amino metabolite (reduction of nitro group) in equine blood and urine for the first time by TLC [128].…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…It is important to obtain such data as nimesulide is used extra-label in equine clinical practice: European legislation (Commission Decision 93/623/CEE amended by Commission Decision 2000/68/CE) permits its use in animals not destined for human consumption, provided such animals are identified. Its use in racehorses is confirmed by the frequent detection of nimesulide and its reduced nitro metabolite (4-amino-2-phenoxy-methanesulphonanilide, 4-APMS) in blood and urine samples taken at the race track (Sarkar et al 1997). This reduced nitro metabolite is weakly active, about 30-fold less so than nimesulide in the carrageenin oedema test in rats (Bernareggi 1998).…”
Section: Introductionmentioning
confidence: 96%